Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/jn/nxaa104
|View full text |Cite
|
Sign up to set email alerts
|

Weight Trajectories After Delivery are Associated with Adiposity and Cardiometabolic Markers at 3 Years Postpartum Among Women in Project Viva

Abstract: ABSTRACT Background Postpartum weight trajectories and its implications on later cardiometabolic health are not entirely understood. Objectives Our objectives were: 1) to characterize maternal weight trajectories from 1 to 24 mo postpartum, 2) to determine the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
1
18
1
Order By: Relevance
“…Similarly, a meta-analysis of observational studies reported that excessive gestational weight gain in singletons was associated with higher mean postpartum weight retention at 3 and ≥15 years postpartum 20 . Other research has linked pregnancy weight gain with postpartum adiposity at 7–8 years 21 , 22 as well as adverse cardiometabolic markers from 3 to 16 years postpartum 23 - 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta-analysis of observational studies reported that excessive gestational weight gain in singletons was associated with higher mean postpartum weight retention at 3 and ≥15 years postpartum 20 . Other research has linked pregnancy weight gain with postpartum adiposity at 7–8 years 21 , 22 as well as adverse cardiometabolic markers from 3 to 16 years postpartum 23 - 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Among Lebanese residents, mean PWR decreased from 7.4 kg to 3.3 kg and the probability of retaining any weight (>0 kg) decreased from 97.1% to 71.3%. In Qatar, an increasing trend in the PWR indicators was observed after delivery and at four months postpartum (mean PWR from 0.9 kg to 3.4 kg and the probability of retaining any weight (>0 kg) from 49…”
Section: Discussionmentioning
confidence: 99%
“…Excess weight retention after pregnancy is preferentially deposited centrally [ 1 , 11 ], and in turn central adiposity is closely linked to insulin resistance and increased cardiovascular disease risk [ 47 , 48 ]. A recent study based on the VIVA project in the US showed that women who retained weight during the first 2 y postpartum developed an adverse cardiometabolic profile 3 years after delivery [ 49 ], characterized by a higher waist circumference, low-density lipoprotein cholesterol and inflammatory markers.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, GWG below the IOM recommendations was associated with a lower weight retention (−2•1 kg, 95 % CI −2•4, −1•9 kg) (14) . Few studies have evaluated the association between GWG and patterns of weight change other from PPWR (11,12) . An analysis of postpartum weight trajectories in Norwegian women found that excessive GWG was associated with two weight trajectories characterised by high initial weight retention (6 months) followed by either weight loss or sustained weight gain through 3 years postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…retention and gain (PPWR þ WG) (i.e. retention of gestational weight, followed by postpartum weight gain) (6,11,12) . We recently showed that PPWR, PPWG and PPWR þ WG were associated with increased adiposity at 6 years postpartum (13) .…”
mentioning
confidence: 99%